Effect of Carbon Content on the Processability of Fe-C Alloys Produced by Laser Based Powder Bed Fusion - Hearn, William; Hryha, Eduard (Frontiers in Materials, 2022)
The present study examines the processability of Fe-C alloys, with carbon contents up to 1.1 wt.%, when using laser based powder bed fusion (LB-PBF). Analysis of specimen cross-sections revealed that lack of fusion porosity was prominent in specimens produced at low volumetric energy density (VED), while keyhole porosity was prominent in specimens produced at high VED. The formation of porosity was also influenced by the carbon content, where increasing the carbon content reduced lack of fusion porosity, while simultaneously increasing the susceptibility to form keyhole porosity. These trends were related to an improved wettability, viscosity, and flow of the melt pool as well an increased melt pool depth as the carbon content increased. Cold cracking defects were also observed in Fe-C alloys that had an as-built hardness ≥ 425 HV. Reducing the carbon content below 0.75 wt.% and increasing the VED, which improved the intrinsic heat treatment during LB-PBF, were found to be effective mitigation strategies to avoid cold cracking defects. Based upon these results, a process window for the Fe-C system was established that produces high density (> 99.8%), defect-free specimens via LB-PBF without the requirement of build plate preheating.